Canada: 2014 Article IV Consultation-Staff Report; Staff Statement; and Press Release (IMF Staff Country Reports, 2015)
KEY ISSUES Economic outlook: The Canadian economy has expanded at a solid pace since 2013, but rebalancing of growth away from household consumption and residential investment remains incomplete, owing mainly to weak business investment. Growth momentum is expected to continue alongside a strengthening U.S. recovery despite substantially lower oil prices. Risks to the outlook are modestly tilted to the downside given sluggish global growth, effects unfolding from sharply lower oil prices, and housing market risks. Key domestic vulnerabilities in housing markets and the household sector remain elevated but contained fro m a financial stability perspective.